Material concreto y las competencias matemáticas en los niños de preparatoria de la Escuela Municipal Básica La Pradera de la ciudad de Loja, periodo 2022– 2023 - Fárez Jadán, Andrea Julissa (2023)
Mathematical competence is the ability to use numbers, shapes, symbols and basic operations, to apply on a day-to-day basis in different environments, solving problems in a coherent and effective way. The objective of this work was to determine how the concrete material strengthens mathematical skills in high school children of the La Pradera Municipal Basic Education School in the city of Loja, period 2022-2023. For the development of the research, the quasi-experimental design was used, a mixed approach to obtain quantitative and qualitative data; and a descriptive scope allowing to know the characteristics of the study population; Likewise, the inductive - deductive method was used to analyze the results, contributing to establish conclusions; and the analytical - synthetic to select relevant information and build the theoretical framework. In the same way, to extract information from the study, the observation technique was used, as an instrument the evaluation scale and the EVAMAT-0 Test, evaluating the level of mathematical competences in children from five to six years of age, obtaining that 100% of the population They were located in a low and medium zone, demonstrating little knowledge in the concepts of geometry, quantity-counting, and problem solving; In order to improve these results, an activity guide was designed and applied through the use of structured and unstructured concrete material, evidencing its effectiveness by reducing the percentage of difficulties to 38%; achieving a significant advance of 62% in the upper zone, reaching the conclusion that the concrete material strengthens the learning of mathematical concepts because the children had the opportunity to manipulate the objects allowing them to build knowledge through experimentation with the senses, encouraging to recognize the characteristics of the elements in order to classify, group, serialize based on their similarities or differences, associate number with quantity, etc., motivating them to learn with these attractive materials. Keywords: Competencies, manipulation, structured material, unstructured material, logical-mathematical reasoning.